2018
DOI: 10.7150/thno.23772
|View full text |Cite
|
Sign up to set email alerts
|

Rich club disturbances of the human connectome from subjective cognitive decline to Alzheimer's disease

Abstract: Alzheimer's disease (AD) has a preclinical phase that can last for decades prior to clinical dementia onset. Subjective cognitive decline (SCD) is regarded as the last preclinical AD stage prior to the development of amnestic mild cognitive decline (aMCI) and AD dementia (d-AD). The analysis of brain structural networks based on diffusion tensor imaging (DTI) has identified the so-called 'rich club', a set of cortical regions highly connected to each other, with other regions referred to as peripheral. It has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
159
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(181 citation statements)
references
References 79 publications
21
159
1
Order By: Relevance
“…Our previous researches con rmed that cognitively normal high-risk individuals of AD have already appeared alterations of brain functional networks (fMRI), white matter networks (DTI) or some re ned areas (sMRI) [46][47][48][49] , suggesting there may be more unmined data of MPMRI in the preclinical stage. As expected, the pure clinical data-based classi cation models were meaningless in this stage, and the traditional volumetric and functional indices are also not sensitive enough (details were presented in the Supplementary Table 5 and Material).…”
Section: Discussionmentioning
confidence: 94%
“…Our previous researches con rmed that cognitively normal high-risk individuals of AD have already appeared alterations of brain functional networks (fMRI), white matter networks (DTI) or some re ned areas (sMRI) [46][47][48][49] , suggesting there may be more unmined data of MPMRI in the preclinical stage. As expected, the pure clinical data-based classi cation models were meaningless in this stage, and the traditional volumetric and functional indices are also not sensitive enough (details were presented in the Supplementary Table 5 and Material).…”
Section: Discussionmentioning
confidence: 94%
“…The preprocessing steps used were as previously described (Bai et al, 2012;Wang X.N. et al, 2016) and were performed using PANDA software as follows: (Ostrom et al, 2014) format conversion of original data (DICOM); (Raysi Dehcordi et al, 2013) the extraction of brain tissue and structure; (Fornito et al, 2013) realignment; (Hart et al, 2016) Eddy current and motion artifact correction of DTI data by applying an affine alignment of each diffusion-weighted image to the b0 image; (Wang et al, 2019) fractional anisotropy (FA) calculation; (Yan et al, 2018) diffusion tensor tractography; and (Iturria-Medina et al, 2011) conduct of tractography to produce 3D streamlines representing fiber tract connectivity (Mori et al, 1999).…”
Section: Preprocessing Of Imagesmentioning
confidence: 99%
“…To characterize the topological organization of WM structural networks at a sparsity threshold, we calculated multiple network metrics of regional nodal characteristics and global network properties. We calculated several graph measures, including global efficiency (E glob ), local efficiency (E loc ), shortest path length (L p ), clustering coefficient (C p ), nodal betweenness (B nod ), nodal degree (K nodal ), nodal efficiency (E nodal ), nodal path length (N Lp ), small worldness (Sigma) (Rubinov and Sporns, 2010), and rich-club organization (Yan et al, 2018). In reference to a previous study (Rubinov and Sporns, 2010), the interpretations of these graph measures are found in Table 2 and Supplementary Material.…”
Section: Network Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This change in distance may be the mechanism of transmission of dynein activation in the doublet MTs [12,19,20]. These studies provide important contributions to our understanding of the ciliary motility as well as cilia-induced fluid motion [21][22][23][24][25][26][27][28]. However, most of the current studies are based on wild-type cilia, and investigations of the ultrastructure and motility of mutant cilia, especially mutant nodal cilia, are still lacking.…”
Section: Introductionmentioning
confidence: 98%